Unique therapeutic project reinforcening the importance of the bond between doctor and patient for adherence to the treatment of chronic diseases: Experience report from medicine students (International Seven Journal of Health Research, 2024)
The population is not limited to the expressions of the illnesses they have. Some obstacles, such as low adherence to treatment, refractory patients, users' dependence on the health service, among others, highlight the complexity of the subjects who use health services and the limits of clinical practice centered on the disease¹. It is well known that the doctor-patient relationship is a fundamental factor for adherence to treatment, always aiming for the best result to improve the quality of life for individuals and the whole community. This relationship is a topic that is currently finding renewed interest in scientific production, training and clinical practice, with the application of communication techniques that can provide better quality care and treatment².